QUALITY OF WORK LIFE: KEPUASAN KERJA PROFESI AKUNTAN - Visnhu Pradana, Bartolomeus Galih (Modus, 2023)
This research will look at eight components Quality of Work Life on job satisfaction of an accountant. For employees to experience a high quality of work life, their needs must be met while they are employed by the organization or company. To achieve job satisfaction, it is very important to consider the demands of employees. One of the key elements in the effective implementation of company activities is representative job satisfaction. 107 accountants working in internal companies, public accountants, government accountants, and accountant educators participated in this study. In this study's quantitative technique and hypothesis testing, PLS-SEM is applied. The outcomes of hypothesis testing revealed five major elements Quality of Work Life - Immediate opportunity to use and develop human capacities, Adequate and fair compensation, Safe and healthy working conditions, The social relevance of work life, and Constitutionalism in the work organization has a significant positive impact on job satisfaction in the accounting profession. However, three main factors Quality of Work Life - Opportunity for continued growth and development, Social in the work organization, dan Work and total life space have a favorable, albeit little, effect on how satisfied accounting professionals is with their jobs. Keywords: Quality of Work Life; Job Satisfaction; Accountant Profession Penelitian ini akan melihat delapan komponen Quality of Work Life pada kepuasan kerja akuntan. Agar karyawan dapat mengalami kualitas kehidupan kerja yang tinggi, kebutuhan mereka harus dipenuhi selama mereka dipekerjakan oleh organisasi atau perusahaan. Untuk mencapai kepuasan kerja, sangat penting untuk memperhitungkan tuntutan karyawan. Salah satu elemen kunci dalam pelaksanaan aktivitas perusahaan yang efektif adalah kepuasan kerja yang representatif. 107 akuntan yang bekerja di internal perusahaan, akuntan publik, akuntan pemerintah, dan akuntan pendidik berpartisipasi dalam penelitian ini. PLS-SEM digunakan dalam metodologi kuantitatif dan pengujian hipotesis penelitian ini. Menurut hasil pengujian hipotesis, lima aspek utama Quality of Work Life - Immediate opportunity to use and develop human capacities, Adequate and fair compensation, Safe and healthy working conditions, The social relevance of work life, dan Constitutionalism in the work organization memiliki dampak positif yang signifikan terhadap kepuasan kerja dalam profesi akuntansi. Namun, tiga faktor utama Quality of Work Life - Opportunity for continued growth and development, Social integration in the work organization, dan Work and total life space memiliki dampak yang positif namun tidak signifikan pada kepuasan kerja profesi akuntan Kata kunci: Quality of Work Life; Kepuasan Kerja; Profesi Akuntan